Kitâb-ı Mukaddes ve Kur'an'ın Sevgi Anlayışı - Yargici, Atilla (Dinî araştırmalar, 2005)
The Bible and The Kor’an says basically the same thing about God’s Love, neigbourhood and brotherhood love, whereas they mentione different ideas about sexual love. Firstly, they announce that man should love God more than the other loved objects like parents, husband-wife and children.The most important manifestation of God’s Love is to obey his rules and to love each other. Secondly, they also indicate brotherhood and neighbourhood love. According to them, God has created entire food and favour for everyone. There is no discrimination between the believer in God or unbeliever in him. So, man should love man without considering who he/she is. Thirdly, while Old Testament mentions sexual love very much, New Testament doesn’t tell us anything about that. However, The Kur’an has expressed that sexual love is a reality of man and it should occur within the marriage